THE IMPLEMENTATION OF ONLINE-BASED LEARNING METHOD IN MADRASAH IBTIDAIYAH NEGERI 2 MATARAM - H.M Zaki (Universitas Islam Negeri (UIN) Mataram, 2020)
The massive and colossal migration from face-to-face learning method to the e-learning method due to the Covid-19 pandemic has become a new challenge for all educators in Mataram Islamic State Elementary School 2. The main challenge is to keep students stays active during the pandemic. This article use a qualitative approach with an explorative study, to reveals the problem of e-learning method. This learning method uses the Google Classroom, Zoom Cloud Meeting and WhatsApp Group as a variant of the learning application. In fact, this method has faced various problems; the parents faced some problems like a lack of funds, time and capability to help their children attending the online class. For students, e-learning is considered harder than face-to-face learning method. Meanwhile for the teacher, the problems were the lack of skills in using gadget and the difficulty of monitoring and controlling the activeness of students during online class.